Supraglottic Neuroendocrine Carcinoma: A Case Report and Literature Review - Renda Alhabib; Chaker Zaidi; Abdulrahman Alfryyan; Hanan Albenayyan; Ibrahim Alotain (Case Reports in Oncological Medicine)
Neuroendocrine neoplasms (NENs) are rare in the head and neck region, with the larynx being the most common site. To date, nearly 700 cases of laryngeal neuroendocrine carcinoma (NEC) have been reported in the literature, with an estimated incidence as low as 0.23%. This type of cancer is more prevalent among men aged 50–83 who are heavy smokers. NENs encompass paragangliomas and epithelial neoplasms. The latter categories include neuroendocrine tumors, or typical carcinoids, and NECs, or atypical carcinoids. Due to their nonspecific and often misleading presentation, and given the rarity of this condition, optimal management lacks standardization. Treatment typically involves a combination of surgery, chemotherapy, and radiotherapy. We present a case of supraglottic laryngeal NEC in a 61-year-old female nonsmoker. The patient underwent endoscopic excision followed by adjuvant radiotherapy.